Naval fleet across-domain communication scheme based on CP-ABE - Wei GUO; Xue-guang ZHOU; Cheng-qin QU; Fang LUO; Xiang-jun JI (Tongxin xuebao)
Attribute-based encryption (ABE) provides a fine-grained access control mechanism and it can realize one-to-many secure communication.Proxy re-encryption can transform an encrypted data to another kind encrypted between different domains.Aiming at the demand of secure communication of across-domain naval fleet,a scheme that based on CP-ABE was proposed.At last,a security analysis of this scheme and an example of the scheme were proposed.This scheme combining the technology of ABE and proxy re-encryption realizes a secure communication of across-domain naval fleet and one-to-many secure communication among the naval fleet.At the meantime,it meets the needs of meet and access of vessel.